Fire safety audit in library buildings / Mohd Najib Tomin - Tomin, Mohd Najib (Faculty of Architecture, Planning and Surveying, 2010)
Fire safety is one of the most important requirements in every types of building in order to protect every single asset in the properties. Fire can occur in any circumstances and regardless of time. Therefore, there are rules and requirement that must be followed to avoid a mishap occurs. Even though, these things always had been neglect by the owner or by the management. This research will cover the inspection and audit on fire safety facilities in library building in order to find out level of maintenance of fire safety facilities. This audit was conducted based on the procedure and practice carry out by Fire Rescue Department. With this research, it will help other parties to do audit by themselves and know the current condition of the fire safety